Clinical nutrition and physical rehabilitation in a long-term care setting: preliminary observations in sarcopenic older patients. Issue 8 (August 2018) - Dimori, Sergio; Leoni, Giorgio; Fior, Luca; Gasparotto, Fulvio
Abstract Background Sarcopenia could have a negative prognostic impact in long-term care residents, which are characterized by multiple comorbidities and a high level of dependence. However, there is limited evidence on its prevalence and management in this healthcare setting. Methods All residents living in a long-term care institution were screened for the presence of sarcopenia. Sarcopenic patients in whom functional status could be assessed were included, based on the Tinetti scale (TS) score, in two parallel single-arm trials and received a specific nutritional supplement for muscle mass recovery in combination (TS ≥ 10) or not (TS < 10) with a supervised physical exercise rehabilitation program for 12 months. The nutritional supplement was administered twice daily for the first 6 months; none for 3 months and again twice daily for the last 3 months. Results We screened 95 residents and 81 had low skeletal muscle mass (SMM) according to bioimpedance. Thirty-nine residents were included in the intervention phase due to sarcopenia. At 6 months, patients receiving nutritional support alone (n  = 17) showed a significant improvement in body weight (P  = 0.009) and composition with an increase in SMM (from 15.3 ± 4.1 to 17.0 ± 5.1 kg, P  = 0.013) and SMM index (SMI; from 6.24 ± 1.07 to 6.91 ± 1.54 kg/m2, P  = 0.013), but not in handgrip strength (HS). Patients assigned to the multidisciplinary program (n = 22) showed an improvement in both muscle mass [SMM (from 16.6 ± 6.0 to 17.3 ± 5.7 Kg, P  = 0.050) and SMI (from 6.63 ± 1.65 to 6.91 ± 1.52 kg/m2, P  = 0.038)] and functional status [HS (from 13.5 ± 5.0 to 15.6 ± 6.7;P  = 0.028), gait speed (from 0.44 ± 0.18 to 0.51 ± 0.20, P  = 0.047) and Short Physical Performance Battery (from 4.6 ± 3.1 to 5.5 ± 3.2, P  = 0.047)] at 6 months. The effect was no longer present after discontinuation of the intervention and was restored after its re-introduction at 12 months. Conclusions Nutritional and multidisciplinary interventions tailored on patient's functional status could be considered as strategies for the management of sarcopenia, a high prevalent condition in old adults living in long-term care institutions.